(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
The fact that deictic phrases play an important role in language ontogenesis makes it difficult to imagine a complete dialogue without these phrases, apart from the fact that they appear in the early stages of infant speech. We often believe that the meaning of linguistic units (e.g., words) is sufficient in teaching language to young children and adults. But such a simplification of language acquisition is a wrong conclusion.”